PRINSIP-PRINSIP MANAJEMEN TENAGA PENDIDIK DAN KEPENDIDIKAN UNTUK MENINGKATKAN MUTU PENDIDIKAN: PRINCIPLES OF EDUCATOR MANAGEMENT AND EDUCATION TO IMPROVE THE QUALITY OF EDUCATION - Syukri, Makmur; Delastri, Yefrineng; Anggraini, Desi; Putri, Desi Sandra; Marzelni, Marzelni (Komunitas Manajemen Kompetitif, 2023)
Abstract: Management of educational personnel, which includes teachers and educational personnel, is a necessity that must be carried out by school administrators in order to utilize educational personnel effectively and efficiently in order to achieve the best results. The ability to search, place, evaluate, direct, motivate and develop the abilities of each teacher and employee, as well as the ability to align individual and organizational goals, are aspects that a school manager is expected to have according to needs. this understanding. The quality of the education and learning process can be studied from two different points of view, namely the quality of the components and the quality of the administration of school institutions. If these components are not managed